Interface behavior of PbO2 on pure lead and stainless steel as anode for dye degradation. Issue 34 (20th July 2016) - Elaissaoui, Ines; Akrout, Hanene; Bousselmi, Latifa
Abstract: PbO2 films are electrodeposited by the galvanostatic (G) and pulsed current (P) methods on lead and stainless steel (AS30), respectively. They are used as electrodes for electrochemical degradation of Amaranth dye. The scanning electron microscope, atomic force microscope, and X-ray diffraction analyses revealed the dominance of β-PbO2 form in two anodes and the absence of the form tet-PbO and PbSO4 in AS30 substrate that have more amorphous shape and less roughness (200 nm). A poor lead oxide adhesion on AS30 substrate is detected. Cyclic voltammetry results showed that the absence of oxidation peak in the case of AS30/PbO2 anode is related to the oxidation of PbSO4 to β-PbO2 . EIS results demonstrated that the pH influences largely PbO2 layer. Concerning E123 degradation, 95 and 91% of color removal (82 and 76% of Chemical oxygen demand removals) were achieved using Pb/PbO2 and AS30/PbO2 anodes, respectively. In this case, current efficiency has kept relatively a high value assuming less energy consumption.